Inovação na poesia americana: e. e. cummings / Innovation in north-american poetry: e.e. cummings - Salman, Daisy Sada Massad (Revista de Letras, 2007)
As letras norte-americanas presenciaram, neste século, um grande renascimento. A poesia, mais do que o romance ou o teatro, foi a grande inovadora, graças à influência exercida por dois americanos: Erza Pound e T. S. Eliot. A ruptura com a tradição já era evidente por volta de 1925. Dentre os vários “novos” poetas, um dos mais bem sucedidos foi, inegavelmente, e.e. cummings. Rejeitou a técnica tradicional e apresentou modificações importantes na retórica tipográfica, na deslocação sintática e na formação de palavras, como atestam os poemas “1(a”, “Portrait” e “anyone lived in a pretty howtown”. Exerceu grande influência sobre os poetas concretistas brasileiros. Presença atuante na literatura americana, é, sem dúvida alguma, um dos grandes inovadores da poesia do século XX. The literature of the United States witnessed a gread renewal in this century. It was poetry, however, much more than fiction or theatre, the innovating genre thanks to the influence of Ezra Pound and T. S. Eliot. They were responsible for the introductionof modernism in England and in America. One of the most successful poets was, undoubtedly, e.e. cummings. He rejected the traditional techniques and presented important changes in the typographical rhetoric, in the syntactic dislocation and in the formation of words, as one can see in his poems: “1(a”, “Portrait” and “ anyone lived in a pretty howtown.” His influence on the Brazilian concret poets was remarkable. He is, certainly, one of the innovators of the English poetry in the twentieth century.